2018
DOI: 10.3989/mc.2018.10716
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of nano-SiO<sub>2</sub> and nano-Fe<sub>2</sub>O<sub>3</sub> on compressive strength, flexural strength, porosity and electrical resistivity in cement mortars

Abstract: The compressive strength, flexural strength, porosity and electrical resistivity properties of cement mortars with nano-Fe2O3 and nano-SiO2 are studied. Amorphous silica is the main component of pozzolanic materials due to its reaction with calcium hydroxide formed from calcium silicate (C3S and C2S) hydration. The pozzolanic reaction rate is not only proportional to the amount of amorphous silica but also to the surface area available for reaction. Subsequently, fine nano-Fe2O3 and nano-SiO2 particles in mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Mitchell et al [43] found unreacted silica fume particles in pastes with 5 % of silica fume after 180 days of curing. This supports the low pozzolanic reaction rate of silica fume due to an agglomeration of nanoparticles [44].…”
Section: Mechanical Performance and Open Porositysupporting
confidence: 69%
See 1 more Smart Citation
“…Mitchell et al [43] found unreacted silica fume particles in pastes with 5 % of silica fume after 180 days of curing. This supports the low pozzolanic reaction rate of silica fume due to an agglomeration of nanoparticles [44].…”
Section: Mechanical Performance and Open Porositysupporting
confidence: 69%
“…It has been reported higher compressive strength in mortars with nano-SiO 2 particles of 40 nm in size than with particles between 12 and 20 nm due to the agglomeration of the small particles [52]. Therefore, the resulting agglomerates will influence on the filling of the capillary pores [44]. Accordingly, nano-SiO 2 particles in a range of 4-8% in mortars can promote an increase in the total porosity [53,54].…”
Section: Alkali-aggregate Mitigation By Pozzolanic Additions In Cemen...mentioning
confidence: 99%
“…Moreover, the unreacted NS particles are dispersed in smaller spaces and fill the void, refining the pore structure, and improving the compactness of the concrete. As previously mentioned, NS particles have extremely large specific surface areas, and when the NS added exceeds the optimal dosage, agglomeration phenomena can occur in the mixture [ 64 ]. Simultaneously, the nanoparticles have strong water absorption; accordingly, excessive NS absorbs the water originally required for the cement hydration, resulting in insufficient cement hydration and a decreased strength of the concrete [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dried and hardened cement paste and mortar have an electrical resistivity of approximately 104–107 Ω·m [36], which is decided by the constituents of cement, humidity, w/c ratio, etc., [37,38]. The resistivity of electrically conductive concrete is under 100 Ω·m [39], depending upon the electronic conduction within the conductive materials, such as steel fibers and graphite.…”
Section: Resultsmentioning
confidence: 99%